Mesenchymal Stromal Cells Express GARP/LRRC32 on Their Surface: Effects on Their Biology and Immunomodulatory Capacity. (18th December 2014) - Carrillo-Galvez, Ana Belén; Cobo, Marién; Cuevas-Ocaña, Sara; Gutiérrez-Guerrero, Alejandra; Sánchez-Gilabert, Almudena; Bongarzone, Pierpaolo; García-Pérez, Angélica; Muñoz, Pilar; Benabdellah, Karim; Toscano, Miguel G.; Martín, Francisco; Anderson, Per
Abstract: Mesenchymal stromal cells (MSCs) represent a promising tool for therapy in regenerative medicine, transplantation, and autoimmune disease due to their trophic and immunomodulatory activities. However, we are still far from understanding the mechanisms of action of MSCs in these processes. Transforming growth factor (TGF)-β1 is a pleiotropic cytokine involved in MSC migration, differentiation, and immunomodulation. Recently, glycoprotein A repetitions predominant (GARP) was shown to bind latency-associated peptide (LAP)/TGF-β1 to the cell surface of activated Foxp3 + regulatory T cells (Tregs) and megakaryocytes/platelets. In this manuscript, we show that human and mouse MSCs express GARP which presents LAP/TGF-β1 on their cell surface. Silencing GARP expression in MSCs increased their secretion and activation of TGF-β1 and reduced their proliferative capacity in a TGF-β1-independent manner. Importantly, we showed that GARP expression on MSCs contributed to their ability to inhibit T-cell responses in vitro. In summary, we have found that GARP is an essential molecule for MSC biology, regulating their immunomodulatory and proliferative activities. We envision GARP as a new target for improving the therapeutic efficacy of MSCs and also as a novel MSC marker. Stem Cells   2015;33:183–195